Starting up seminarmedis.com a new medical event management and information system - Smartanto, Nico; S. Gunawan, Benny (The Indonesian Journal of Business Administration, 2019)
AbstractSeminar Medis is a startup company developing medical event management and information system. The main problem that the Seminar Medis will solve is how a doctor can easily search, register and pay for medical seminars. To date there’s no centralize place for doctors to find the seminars and workshop they need and want. The majority of doctors get information about medical seminars are from social media and group chat. This research begins by discovering problems experienced by doctors and seminar organizers in conducting seminars. Search is done by collecting data from interviews and filling out questionnaires. The next step is to analyze potential market conditions and analyze competition using Porter 's Five Forces. To solve this problem Seminar Medis made MVP (Minimum Viable Product) and tested it whether the product was able to solve the problem for the customer. The minimum product used for the first time is through Instagram social media. The solution to this research is to find how Seminar Medis can grow as startups company. To be able to achieve that Seminar Medis formulate a business model by using Business Model Canvas to run its business strategy and develop its products to support the business model. The next implementation plan is to develop the website as main product to make business model work. Keywords: seminar medis, startup company, doctor, business model.